10–7 Human error in practical procedures. (17th November 2017) - Nathoo, S; Dev, S; Thomas, B; Laws-Chapman, C
Abstract : Introduction and Aims: Doctors are required to achieve competency in a set of skills. Traditionally these have been 'learnt' on the job. The introduction of the European Working Time Directive has resulted, for UK doctors in training, in reduced patient exposure and supervision. With patient safety now at the forefront of our practise, the 'see one, do one, teach one' method of acquiring skills is no longer acceptable. The resulting lack of knowledge may then expose patients to harm. Procedural skills competence is important, but so is the knowledge of the impact human factor skills (HFS) has on patient safety. These skills are recognised factors contributing to mistakes (Rodriguez-Paz et al., 2009). Our course design combines procedural skill teaching with HFS teaching. To our knowledge this is the first programme of its kind in the UK. The aim is to provide an environment in which skill based competencies are integrated with HFS knowledge to allow skills to be performed without patient safety being affected. Methods: The course accommodates doctors at any stage of their training. The morning consists of four practical procedures– chest drain, lumbar puncture, central line and nasograstric tube insertion, taught by an expert instructor providing real-time feedback to trainees. The skills chosen are based on Serious Untoward Incidences (SUI's) at our trust alongside consideration of emergency procedures. Consent processes, guidelines and identity checking are explored prior to practising each procedure. A maximum of 12 trainees per course ensures adequate time for hands-on practise. The afternoon is spent understanding and exploring the impact of human factors on performing the procedures. Trainees are then encouraged to apply the human factor skills learnt to the procedural skills practised earlier in the day in order to explore ways to reduce error in practice. Results: Data collection involves feedback from participants, asking specifically about whether the skills stations improved their knowledge and whether the afternoon session added to learning. Thematic analysis of the results show a self-assessed improved confidence in knowledge on performing practical procedures, with a greater understanding of the impact of human factors. Conclusion: Combining procedural skills training and HFS learning improves trainee confidence in performing procedures and increases understanding about the human factors that contribute to procedural error and patient harm. This has the potential to improve patient safety. Our aim would be to run this course in the future. We hope to be able to perform a comparison study in order to fully assess any additional impact that this combined course has on reducing patient harm compared to a procedural course alone. In addition we hope to be able to collect in-situ data in order to conduct a level 3 Kirkpatrick evaluation. References: Rodriguez-Paz, et al. Beyond 'see one, do one, teach one': Toward a different training paradigm. Qual Saf Health Care2009;18:63–68. Kirkpatrick DL. Evaluating training programs : The four levels (3rd ed.) 2005. Williston: Berrett-Koehler.